PENERAPAN PENDIDIKAN KARAKTER ISLAMI MELALUI HADIST-HADIST PENDEK PADA SISWA KELAS I DI SD MUHAMMADIYAH 5 SAMARINDA - Ratna Khairunisa; Gamar Al Haddar (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
This study aims to determine the application of Islamic character education through short hadits at Muhamadiyah 5 Elementary School in Samarinda. This type of research is descriptive qualitative research. Instrument in this study is the researcher himself. The data collection techniques used include observation, interviews and documentationThe results of the study show that (1) primary schools are the second socialization environment for children to learn to interact with their peers and with adults. From this interaction the child experiences various kinds of positive and negative knowledge and behavior. Experience and behavior that children get when interacting at school will be more and varied than the experiences and behaviors they receive at home. In this case the school optimizes children's Islamic moral and values development through short hadiths taught by the teacher in teaching and learning activities as an effort to instill Islamic character in children by introducing short hadist on children (2) Short hadist introduced are short hadist simple and easy to memorize, among others, hadist relating to cleanliness, hadist prohibited from eating and drinking while standing, hadist about honesty, hadist about hygiene and others. (3) The introduction of a short hadist from an early age makes students more polite in behaving and appreciating people in their environment. Keywords: Islamic Character Education & Short Hadist